PERSEPSI SISWA TERHADAP LAYANAN KONSELING INDIVIDUAL PADA SISWA KELAS XI SMA STELLA DUCE 2 YOGYAKARTA TAHUN AJARAN 2022/2023 - Devani Putri, Vincensia Amara; Setyandari, A. (SOLUTION, 2024)
This research aims to: (1) describe class XI students' perceptions of individual counseling services at SMA Stella Duce 2 Yogyakarta, (2) find out suggestions for guidance topics to help students understand and have a good perspective on individual counseling services. This type of research is quantitative descriptive. The research subjects were 88 class XI students of SMA Stella Duce 2 Yogyakarta. Data collection used a perception scale with 49 valid items and had a Cronbach Alpha reliability index of 0.925. The data collection technique uses a questionnaire with a Likert scale and is arranged based on aspects of perception: (1) affective, (2) conative, (3) cognitive. The results of the research show that there is a perception of students participating in individual counseling services in class individual at school. Then, in the perception item scores there are 26 (53.10%) perception items in the very good category, then there are 2 (4, 10%) perception items in the good category, there are 4 (8.20%) perception items in the sufficient category, and 17 items in the poor category (34.70%). Researchers propose guidance topics based on poor item scores with affective aspects (6 items), conative aspects (6 items), and cognitive aspects (5 items).